New classification focusing on the relationship between the attachment of the iliofemoral ligament and the course of the fracture line for intertrochanteric fractures. Issue 8 (August 2016) - Futamura, Kentaro; Baba, Tomonori; Homma, Yasuhiro; Mogami, Atsuhiko; Kanda, Akio; Obayashi, Osamu; Sato, Kazuo; Ueda, Yasuhisa; Kurata, Yoshiaki; Tsuji, Hideki; Kaneko, Kazuo
Abstract: Purpose: There are various types of intertrochanteric fractures that are unstable pertrochanteric fractures of the hip. The aim of this study was to develop a systematic and comprehensive classification of intertrochanteric fractures. Materials and methods: This study enrolled 74 patients with intertrochanteric fractures treated by us between 2012 and 2015. The fractures were classified using 3D-CT images taken immediately after the fractures occurred based on the course of the lateral fracture line (LFL) that extends through the lateral femoral cortex distal to the vastus ridge of the greater trochanter in the intertrochanteric area. Furthermore, the presence or absence of additional typical fractures was also studied. Then, 4 orthopedic specialists examined the 3D-CT images of 20 patients randomly selected from the 74 patients to evaluate both the inter-rater and intra-rater agreement levels. Results: Intertrochanteric fractures were classified into three types according to the LFL patterns. Type I (41.9%), the Lateral Wall Pattern, has a LFL that extends towards the lateral fiber bundle attachment area of the iliofemoral ligament. Type II (24.3%), the Transverse Pattern, has a LFL that extends towards the medial bundle attachment area. Type III (33.8%), the Reverse Oblique Pattern, has a LFL that extends between the lateral and medial fiber bundle area of the iliofemoral ligament. Each type showed characteristic displacement and was associated with various combinations of typical fractures (fracture across the intertrochanteric line, posteromedial fragment, including the lesser trochanter, posterolateral fragment posterior to the femoral greater trochanter, and banana-shaped big fragment, including both the greater trochanter and the lesser trochanter). The mean κ values for the interobserver and intraobserver agreement levels were 0.77 (0.70–0.85) and 0.76 (0.70–0.85), respectively, which were considered substantial agreement levels. Conclusion: We believe our new classification is a useful communication tool for medical professionals in the diagnosis of fractures.